Temporal trends and patterns in atrial fibrillation incidence: A population-based study of 3·4 million individuals - Jianhua Wu; Ramesh Nadarajah; Yoko M. Nakao; Kazuhiro Nakao; Chris Wilkinson; Mamas A. Mamas; A. John Camm; Chris P Gale (2022)
Population-based studies of atrial fibrillation (AF) incidence are needed to inform health-service planning, but evidence is conflicting. We assessed trends of AF incidence in a large general population cohort from England.